Development of an instrument to measure EFL teachers’ perceptions of reflective teaching - Moghaddam, Rokhsareh Ghorbani (Universitas Pendidikan Indonesia, 2019)
Given the importance of reflective practice in education, little research has been done to investigate how EFL teachers and EFL learners perceive reflective teaching. Since reflection calls for disclosing the underlying views, understandings, and beliefs behind actions on the part of teachers, it is expected that the teachers can provide some deeper insights into reflective teaching employed in their classroom (Richards Lockhart, 1996). The study was undertaken in light of current psychometric thinking about how a new instrument should be validated. The aim of the current research was to construct and validate an instrument measuring EFL teachers’ perceptions of reflective teaching. Through inquiry in the review of the related literature and interview with EFL teachers and EFL learners, a reflective teaching perception questionnaire was constructed in a five-point Likert scale format. In order to establish the construct validity of the new questionnaire, it underwent factor analysis with a sample of 200 EFL teachers and 100 EFL learners. The piloting and testing of the tentative scale through exploratory and confirmatory data analyses reduced the instrument to an 8-factor model with 37 items. By means of Cronbach’s alpha, the reliability of the instrument was obtained to be 0.916. The results of factor analyses yielded the dimensions of technicality, criticality, inquiry, creativity, teacher’s characteristics, learner’s factors, advantages of reflective teaching, and obstacles to reflective teaching. The study provides some applications of this instrument in the context of language teaching as well.